KEHIDUPAN PEDAGANG SAYURAN KOMUTER ETNIS MINANGKABAU (Studi Kasus Migran Pedagang Sayur di Pasar Simpang Baru Kecamatan Tampan Kota Pekanbaru) - Muhammad Irham; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Increased means of transformation, communication, and technological advances in infrastructure have an effect on the volume and direction of population migration, which makes the distance between regions relatively shorter and smoother, the greater the migration flow. Migration triggers overcrowding and causes poverty and unemployment in urban areas. Generally these migrans work in the informal market sector, namely as traders in the market. The Minangkabau Ethnic traders chose to trade and migrate for reasons of their residence and family who lived in the cities of West Sumatra, so they returned home from West Sumatra to Pekanbaru City. Most of the traders who migrate are Minangkabau Ethnic vegetable traders. They migrate back and forth because of economic factors, so that makes researchers want to know why Minangkabau traders migrate only to trade and find out more details about the socio-economic vegetable traders who migrate back and forth in the Simpang Baru Market, Pekanbaru. Using Everett S. Lee migration, migration is looking at Push Factors and also Pull Factors. Using qualitative descriptive method of study by conducting in-depth observations and interviews with 1 key informant and 4 informants. The result of this study indicate that Minangkabau traders migrate based on informans answers because of the low price of vegetables in they yard, while the pull factors is because of the strategic and crowded condition of the Simpang Baru Pekanbaru City. While the socio-economic traders in Simpang Baru Market are well established marked by mutual greeting, reprimand, and exchanging merchandise. The economics of the Minangkabau vegetable trader at the Simpang Baru Market is that it can be seen from the considerable benefits that their vegetables always sell out. Keywords: Migration, Minangkabau Ethnic, Vegetable Commuter Traders